2014
DOI: 10.3389/fnhum.2014.00655
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological evidence for functionally distinct neuronal populations in the human substantia nigra

Abstract: The human substantia nigra (SN) is thought to consist of two functionally distinct neuronal populations—dopaminergic (DA) neurons in the pars compacta subregion and GABA-ergic neurons in the pars reticulata subregion. However, a functional dissociation between these neuronal populations has not previously been demonstrated in the awake human. Here we obtained microelectrode recordings from the SN of patients undergoing deep brain stimulation (DBS) surgery for Parkinson's disease as they performed a two-alterna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 41 publications
4
32
0
Order By: Relevance
“…We found that MS neurons were on average characterized by longer waveforms compared to non-MS neurons (1.15 ± 0.23 ms versus 0.96 ± 0.32 ms; waveform length was measured as the time that elapsed between the two positive peaks [ 14 ] of the waveform; t [65] = 2.65, p = 0.012, permutation t test; Figures 3H and 3I ). Additionally, MS neurons satisfied the criteria for DA neurons established by previous work: 15/17 MS neurons had waveforms longer than 0.8 ms and firing rates lower than 15 Hz [ 14 , 41 ]. We also found that the recording sites where MS neurons were identified were predominantly in the dorsal parts of the SN ( Figures 1D and 1E ).…”
Section: Resultsmentioning
confidence: 78%
“…We found that MS neurons were on average characterized by longer waveforms compared to non-MS neurons (1.15 ± 0.23 ms versus 0.96 ± 0.32 ms; waveform length was measured as the time that elapsed between the two positive peaks [ 14 ] of the waveform; t [65] = 2.65, p = 0.012, permutation t test; Figures 3H and 3I ). Additionally, MS neurons satisfied the criteria for DA neurons established by previous work: 15/17 MS neurons had waveforms longer than 0.8 ms and firing rates lower than 15 Hz [ 14 , 41 ]. We also found that the recording sites where MS neurons were identified were predominantly in the dorsal parts of the SN ( Figures 1D and 1E ).…”
Section: Resultsmentioning
confidence: 78%
“…In a previous study, we showed that SN single-units that demonstrated firing rates slower than 15 Hz and waveform durations >0.8 ms demonstrated post-feedback responses consistent with DA neurons, whereas units that demonstrated high spike rates (>15 Hz) and narrow waveforms (<0.8 ms) demonstrated post-feedback responses consistent with GABAergic neurons (Ramayya et al, 2014b), a finding consistent with prior non-human primate studies (Matsumoto and Hikosaka, 2009). …”
Section: Methodsmentioning
confidence: 85%
“…Third, whereas molecular analysis of STN and GPi-obtained BTIs may be of interest to investigate functional changes occurring in PD, other structures bearing alpha-synuclein pathology, like the SNpc, might be more relevant to address pathogenesis. Indeed, because the SN lies anatomically just below the STN, it is not unusual for the tip of the DBS electrode to be placed within the SN [ 33 ], and we therefore assume that BTIs can also be captured from this pivotal structure in certain patients.…”
Section: Discussionmentioning
confidence: 99%